2016
DOI: 10.7150/jca.15170
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Enhancement of Anticancer Activity of Caffeic Acid Phenethyl Ester by γ Cyclodextrin

Abstract: Caffeic Acid Phenethyl Ester (CAPE) is a key component in New Zealand propolis, known for a variety of health promoting and therapeutic potentials. We investigated the molecular mechanism of anticancer and anti-metastasis activities of CAPE. cDNA array performed on the control and CAPE-treated breast cancer cells revealed activation of DNA damage signaling involving upregulation of GADD45α and p53 tumor suppressor proteins. Molecular docking analysis revealed that CAPE is capable of disrupting mortalin-p53 com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
100
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(104 citation statements)
references
References 67 publications
4
100
0
Order By: Relevance
“…As a phenolic constituent derived from honeybee propolis, CAPE possesses great anti-inflammatory activities and can suppress the proinflammatory cytokines production and enhance epithelial barrier function, which could be a potential therapeutic agent for IBD (17,18). However, the unstable chemical property, low water solubility and the poor bioavailability of CAPE limit its efficacy (19)(20)(21). Therefore, in order to enhance the water solubility, chemical stability and pharmacological activity of CAPE, FA-97 was newly synthesized by introducing a D-glucose into CAPE to construct a glucosidic bond (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a phenolic constituent derived from honeybee propolis, CAPE possesses great anti-inflammatory activities and can suppress the proinflammatory cytokines production and enhance epithelial barrier function, which could be a potential therapeutic agent for IBD (17,18). However, the unstable chemical property, low water solubility and the poor bioavailability of CAPE limit its efficacy (19)(20)(21). Therefore, in order to enhance the water solubility, chemical stability and pharmacological activity of CAPE, FA-97 was newly synthesized by introducing a D-glucose into CAPE to construct a glucosidic bond (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that CAPE possesses no known side effects (17) and could be a potential therapeutic agent for IBD by suppressing pro-inflammatory cytokines production and enhancing epithelial barrier function (18). However, the CAPE molecule can be decomposed easily in biological systems on account of its ester bond (α-β unsaturated carbonyl) and the catechol groups (19).…”
Section: Introductionmentioning
confidence: 99%
“…Besides these, over 150 constituents, including flavonoids, phenolic acids, esters, terpenoids, steroids, amino acids and cinnamic acid derivatives have been identified (3), and are hence considered as popular pharmacological research material (4). A broad spectrum of biological activities identified in propolis include antitumor (5)(6)(7)(8)(9)(10)(11)(12), anti-inflammatory (13)(14)(15), anti-bacterial (16)(17)(18), anti-viral (16,19,20) and anti-fungal (16) activities. Propolis is used in cosmetic products, such as body lotions, ointments, face creams and in functional food in various forms, such as tablets, capsules, toothpaste and mouthwash preparations (21).…”
Section: Introductionmentioning
confidence: 99%
“…CAPE and ARC have been reported to differ in their bioavailability profile that in turn is determined by the stability of the compounds to the digestive enzymes and absorption through the intestinal lining. CAPE alone becomes degraded by secreted esterases (12); however, when combined with γ cyclodextrin (γCD) it is protected and has improved activity in in vitro and in vivo antitumor assays (12). On the other hand, ARC has been reported to possess extremely low absorption efficiency and bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Although this initial pilot study did not seek to determine the mechanisms of action, previous reports of the anti-oxidant, anti-mitogenic, and anticarcinogenic properties of CAPE suggest that some of the mechanisms responsible for these effects include the inhibition of NFkB, lipid peroxidation, protein tyrosine kinase, ornithine decarboxylase, and matrix metalloproteinase (MMP)-9 catalytic activity. [21][22][23] Other studies have revealed that enhanced expression and activation of the tumor suppressor p53 and activation of pro-apoptotic Bax and caspase-3 may also be induced by CAPE administration. 24,25 These results must also be viewed in context of the limitations that were intrinsic to this type of pilot study.…”
Section: Discussionmentioning
confidence: 99%